Предмет: Алгебра,
автор: Аноним
Преобразуйте выражение в многочлен стандартного вида:
а). 2(a-1)²+3(a-2)²
б). 5(x-y)²+(x-2y)²
ПОЖАЛУЙСТА СРОЧНО НАДО!
Ответы
Автор ответа:
0
А) условие= 2(a^2-2a+b)+3(a^2-4a+4)=
=2a^2-4a+2+3a^2-12a+12=
=5a^2-16a+14
=2a^2-4a+2+3a^2-12a+12=
=5a^2-16a+14
Автор ответа:
0
2(а^2-2a+1)+3(a^2-4a+4)
2a^2-4a+2+3a^2-12a+12
5a^2-16a+14
5(х^2-2xy+y^2)+(x^2-4xy+4y^2)
5x^2-10xy+5y^2+x^2-4xy+4y^2
6x^2+9y^2-14xy
2a^2-4a+2+3a^2-12a+12
5a^2-16a+14
5(х^2-2xy+y^2)+(x^2-4xy+4y^2)
5x^2-10xy+5y^2+x^2-4xy+4y^2
6x^2+9y^2-14xy
Похожие вопросы
Предмет: Қазақ тiлi,
автор: kuntuganskaaajymka
Предмет: Русский язык,
автор: ekaterinakulagina52
Предмет: Математика,
автор: kentyice2020
Предмет: Математика,
автор: Варя2105